The labor arbitration process - Fleming, R. W. (Urbana : University of Illinois Press, 1965)
This volume will be of primary interest to those already at work in the labor arbitration. The author, a professor of law, is concerned with spelling out the current problems of labor arbitration. These problems are the themes of succeeding chapters: sharing of costs, time lag in decisions, excessive formalization, paucity of new, young arbitrators, and finally, individual rights vis-à-vis the powers of union organization. A brief historical chapter traces the evolution of the arbitration technique of resolving labor-management problems. This material serves as a preface to Fleming's discussion of the immediate problems of the field.
Includes bibliographical footnotes.
rpm 21/03/2018
Loans
Keywords: Arbitration, Industrial